2020
DOI: 10.4274/tjo.galenos.2020.85282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Optic Disc and Macula in Healthy Children Using Optical Coherence Tomography Angiography

Abstract: Objectives: To perform the measurements of the optic disc and macula in healthy children using optical coherence tomography angiography (OCTA) in order to determine the normative data values and compare these by age, gender, spherical equivalent (SE), and axial length (AL). Materials and Methods: A total of 146 eyes belonging to 146 healthy children (74 girls, 72 boys) aged 6 to 16 years were included in this prospective study. Refraction and biometry measurements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
2
12
1
Order By: Relevance
“…Unlike previous studies [ 6 8 , 18 , 26 ], our research found no correlation between FAZ and CMT. The difference may be attributed to unadjusted results to certain major confounders in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unlike previous studies [ 6 8 , 18 , 26 ], our research found no correlation between FAZ and CMT. The difference may be attributed to unadjusted results to certain major confounders in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Some research results indicated that adult females had higher FAZ than males, which can also be seen in children as in our study [ 8 , 19 , 23 , 25 , 26 ]. Other studies reported no significant difference between the sexes [ 18 , 25 , 26 ]. In our study, accounting our smaller number of female subjects, the median of FAZ was 0.28 mm (range 0.02–5.05) in male and 0.37 mm (range 0.05–1.08) in female.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…While the correlation analyzes ( Supplementary Table 1 ) found girls had significantly larger FAZ area than boys and VD at the fovea in the SCP and DCP was significantly greater in boys. This close relationship between FAZ size and sex were greatly consistent with the children studies by İçel et al ( 23 ) and Kiziltoprak et al ( 11 ). The difference in the area and perimeter of FAZ values between different studies may be due to this sex ratio, in addition to different devices, measurement methods, algorithm version, sample size and ethnicity.…”
Section: Discussionsupporting
confidence: 91%